Tablero didáctico de control de iluminación mediante mini PLC logo (PROGRAMA LÓGICO DE CONTROL). - Sarango Gualán, Claudio Aníbal (2010)
The present investigation topic is a contribution to the NATIONAL UNIVERSITY DE LOJA, to the students of the electricity career and the electric shop of the Area of Energy the Industries and Natural Resources not Renewable The investigation allowed to fulfill the general objective that is to offer basic knowledge of how it can improve the control of illumination electronic mediating devices as it is it MINIPLCLOGO, keeping in mind the different applications like they are it: facilities electric domiciliares, residential and industrial. The board has as main function the teaching to the students of the different methods for the control of mediating illumination a PLC (it PROGRAMS LOGICAL OF CONTROL) without discarding assimilation of knowledge and the methodology used for the development of the work the observation, which had a guide that will allow to carry out in efficient several way practices according to the designed pattern. As general conclusion we have ended up deducing that the students should have technician-practical boards, which allow to carry out practice of control mediating illumination the programming of an electronic device as it is it the LOGO and to offer advice theoretical-practices of all elements that conform didactic board that which will allow a better conservation and effectiveness of the same one.